Students’ Grammatical Cohesion in Essay Writing - Abdulhalim Daud; Ali Ajam; Naniek Jusnita (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
Cohesion plays an essential part in writing. This study aims to find out what grammatical cohesion device students used in writing. This study is a qualitative study. It was conducted during the semester. Fifteen university students studying essay writing participated as participants of this study. The students’ writing drafts were collected and analyzed. Content analysis was applied. The results showed that the students use two grammatical cohesion devices in their essay writing; references and conjunction. References consist of personal references, demonstrative references, and comparative references while conjunction consists of additive conjunction, adversative conjunction, causal conjunction, and temporal conjunction. On the other hand, there were two grammatical devices that were not found in students writing draft substitution and Ellipsis devices. Thus, those two devices are mostly found in oral communication. It means that the analyzed passages do not expose all of the cohesion devices sufficiently and provide too many highlights on one type which is the reference. This fact showed that the sentences within the text should not be connected by the existence of all cohesion devices. Some of the adequate devices were as much as necessary to create a series of sentences called a text. Some presence of them is already enough to create cohesion.